Preembolization superselective angiography: role in the treatment of brain arteriovenous malformations with isobutyl-2 cyanoacrylate. - Viñuela, F; Fox, A J; Debrun, G; Pelz, D (American Journal of Neuroradiology, 1984)
Transfemoral and intraoperative embolization of arteriovenous malformations (AVMs) of the brain with isobutyl-2 cyanoacrylate may achieve complete and permanent occlusion of the AVMs. The preembolization superselective angiogram is an important source of information to decrease potential technical or clinical complications while seeking that goal. The information obtained from the angiogram of each individual feeder may be classified as anatomical, dynamic, and functional. This angiogram is performed either through a calibrated-leak balloon glued to a Silastic tubing, which is capable of negotiating cortical arterial curves, or through a short catheter directly placed into a feeder at surgery. In 64 patients, 175 preembolization superselective angiograms were obtained. Of those, 105 were obtained using the transfemoral technique, and 70 were obtained by direct catheterization after a craniotomy. Complications occurred in eight patients with only one permanent injury. Transient neurologic deficit occurred in five patients. One patient developed a permanent left monoplegia and one patient a subarachnoid hemorrhage without permanent neurologic deficit. In one patient, a delayed intracerebral hemorrhage produced a right hemiplegia and aphasia. The patient fully recovered in 6 months.